A micromechanical-based model of stimulus responsive liquid crystal elastomers. (1st June 2021) - Brighenti, Roberto; McMahan, Connor G.; Cosma, Mattia P.; Kotikian, Arda; Lewis, Jennifer A.; Daraio, Chiara
Abstract: Stimulus responsive elastomers are advanced engineered materials that perform desired functionalities when triggered by external stimuli. Liquid crystal elastomers (LCEs) are one important example that exhibit reversible actuation when cycled above and below their nematic-to-isotropic transition temperature. Here, we propose a micromechanical-based model that is centered on the evolution of the chain distribution tensor of the LCE network. Our model, framed within the statistical model of the chain network, enables a mesoscale description of their mechanical response under an external thermal stimulus. We compare the model to prior experimental observations of the bending response of 3D printed LCE elements with controlled director alignment.